(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to identify the design thinking skills of the students of the Department of Mathematics in the Colleges of Education. To verify the aim of the research, put the following questions and hypotheses:1) What is the level of design thinking skills among the students of the Mathematics Department (fourth stage/morning) in the faculties of education?2) There is no statistically significant difference at the level of significance (0.05) between the mean scores of male and female students for the mathematics departments (the fourth stage) in the colleges of education. The research sample consisted of (294) male and female students from the mathematics departments / fourth stage in the colleges of education For the first semester of the academic year (2021-2022), the College of Basic Education of Al-Mustansiriya University and the University of Kufa were chosen as a basic sample in a stratified random manner, and the research tool was prepared, namely: Design Thinking Skills Test consisting of (10) essay problems (each problem included five paragraphs sub for design thinking skills), and the results showed the following:1) The weak level of design thinking skills among the students of the faculties of education in the mathematics departments / fourth stage2) There is a statistically significant difference at the level of significance (0.05) in design thinking skills between males and females in the faculties of education, mathematics departments / fourth stage, in favor of females.In the light of the results of this research, some recommendations can be made that may contribute to some extent in improving the level of design thinking among students, namely:A) Reconsidering the formulation of curricula in the faculties of education in accordance with the requirements to raise the level of design thinking skills among students of mathematics departments in a manner that takes into account individual differences in terms of the logical arrangement and sequence of information.b) Enriching the mathematical curriculum in the faculties with various activities that motivate students to think designally. Also some suggestions can be madeA) Carrying out studies similar to this research dealing with students of the four stages in mathematics departments in other universities.b) Examining the relationship between design thinking skills and achievement among university students in the faculties of education.Keywords: design thinking, college of basic education.